Tax policy and entrepreneurial entry with information asymmetry and learning - Diego d'Andria (European Commission, Joint Research Centre (JRC), 2017)
We study a market with entrepreneurial and workers entry where both entrepreneurs' abilities and workers' qualities are private information. We develop an Agent-Based Computable model to mimic the mechanisms described in a previous analytical model (Boadway and Sato 2011). Then, we introduce the possibility that agents may learn over time about abilities and qualities of other agents, by means of Bayesian inference over informative signals. We show how such different set of assumptions affects the optimality of second-best tax and subsidy policies. While with no information it is optimal to have a subsidy to labour and a simultaneous tax on entrepreneurs to curb excessive entry, with learning a subsidy-only policy can be optimal as the detrimental effects of excessive entrepreneurial entry are (partly or totally) compensated by surplus-increasing faster learning.
Keywords: D82; D83; G14; H25; 330; Entrepreneurship; Taxation; Asymmetric Information; Learning; Adverse Selection; Agent-Based Computational Model